Jet Grouting Underpinning Of A Building In The US - Gustavo E. Armijo (Deep Foundations Institute, 2002)
This job was done in Morristown, NJ, with mono fluid system jet grouting for the construction of a new bank building. After the demolition of the existing two story structures, an excavation in loose sandy fill materials was necessary in order to reach the new structure basement level. Due to this jet grouting was selected as a medium to provide both excavation support and permanent underpinning, minimizing the adjacent building settlements. These two adjacent buildings were partially underpinned with a "gravity wall" made with 2 and 3 rows of secant vertical and inclined jet grout columns. Besides the classical jet grouting control methods, during the jet grouting execution, all the drilling and grouting parameters were recorded by a proprietary system called "Slogger". Additionally, after the jet grouting execution, an innovative result control technique was used by means of the application of the same parameter recording system. Some of the production columns were re-drilled and a comparison was made between the obtained drilling parameters and those obtained for the same age test columns. Under the referred existing conditions and in comparison with the conventional underpinning techniques, this project demonstrated that jet grouting, with proper execution and result control, can be faster than them and can maintain the building structural stability and act, at the same time, as a retention system minimizing the existing building settlements.